Effects of potassium content on the electrical and mechanical properties of (Na1-xKx)0.5Bi0.5TiO3 thin films. Issue 3 (April 2015) - Zhan, K.; Zheng, X.J.; Peng, J.F.; Zhu, Y.K.; Cheng, H.B.
Abstract: (Na1- x K x )0.5 Bi0.5 TiO3 (NBT-KBT-100 x ) thin films with different potassium contents ( x =0.15, 0.18, 0.20, 0.25) were fabricated on LaNiO3 /SiO2 /Si(100) substrate by metal-organic decomposition, and the effects of potassium content on piezoelectric, dielectric, and mechanical properties of the thin films were investigated by scanning probe microscopy, impedance analyzer, and nanoindenter, respectively. The residual stress was evaluated by the orientation average method to clarify the dependence on potassium content, and it is used to understand the piezoelectric enhancement mechanism. Among the thin films, NBT-KBT-15 thin film is of the largest piezoelectric coefficient of 95 pm/V, dielectric constant of 240, elastic modulus of 203.61 GPa, and hardness of 12.36 GPa while NBT-KBT-25 thin film is of the largest residual compressive stress 270 MPa. The enhanced electrical properties are attributed to coexistent phases, fine grain, and lattice mismatch, respectively.